DNAJ Proteins in neurodegeneration: essential and protective factors. (19th January 2018) - Zarouchlioti, Christina; Parfitt, David A.; Li, Wenwen; Gittings, Lauren M.; Cheetham, Michael E.
Abstract : Maintenance of protein homeostasis is vitally important in post-mitotic cells, particularly neurons. Neurodegenerative diseases such as polyglutamine expansion disorders—like Huntington's disease or spinocerebellar ataxia (SCA), Alzheimer's disease, fronto-temporal dementia (FTD), amyotrophic lateral sclerosis (ALS) and Parkinson's disease—are often characterized by the presence of inclusions of aggregated protein. Neurons contain complex protein networks dedicated to protein quality control and maintaining protein homeostasis, or proteostasis. Molecular chaperones are a class of proteins with prominent roles in maintaining proteostasis, which act to bind and shield hydrophobic regions of nascent or misfolded proteins while allowing correct folding, conformational changes and enabling quality control. There are many different families of molecular chaperones with multiple functions in proteostasis. The DNAJ family of molecular chaperones is the largest chaperone family and is defined by the J-domain, which regulates the function of HSP70 chaperones. DNAJ proteins can also have multiple other protein domains such as ubiquitin-interacting motifs or clathrin-binding domains leading to diverse and specific roles in the cell, including targeting client proteins for degradation via the proteasome, chaperone-mediated autophagy and uncoating clathrin-coated vesicles. DNAJ proteins can also contain ER-signal peptides or mitochondrial leader sequences, targeting them to specific organelles in the cell. In this review, we discuss the multiple roles of DNAJ proteins and in particular focus on the role of DNAJ proteins in protecting against neurodegenerative diseases caused by misfolded proteins. We also discuss the role of DNAJ proteins as direct causes of inherited neurodegeneration via mutations in DNAJ family genes. This article is part of the theme issue 'Heat shock proteins as modulators and therapeutic targets of chronic disease: an integrated perspective'.